2017
DOI: 10.1111/psyg.12267
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous usage of dementia medications and anticholinergics among Asians and Pacific Islanders

Abstract: Simultaneous prescribing of cholinesterase inhibitors, memantine, and anticholinergic medications was significantly less common than in previous studies, with some ethnic variability. The less frequent occurrence of concurrent medications in the Asian population may be because of variations in the rate of indications or in tolerability for anticholinergic medications among the population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Two studies reported on potentially inappropriate medication use—“drugs that should generally be avoided because they are ineffective or pose an unnecessarily high risk for older adults, and drugs that are appropriate to use in older persons only at certain doses, frequencies, or duration of therapies.” 58 One study reported higher rates of potentially inappropriate medication use in Hispanic Americans compared to NHW persons 58 and another found higher rates of concurrent use of medications with anti‐cholinergic properties and anti‐dementia medications in NHW and Native Hawaiians compared to Asian Americans 59 . Finally, several studies reported racial/ethnic differences in patterns of use of drugs for hypertension and other medical conditions in PLWD 46,60,61 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies reported on potentially inappropriate medication use—“drugs that should generally be avoided because they are ineffective or pose an unnecessarily high risk for older adults, and drugs that are appropriate to use in older persons only at certain doses, frequencies, or duration of therapies.” 58 One study reported higher rates of potentially inappropriate medication use in Hispanic Americans compared to NHW persons 58 and another found higher rates of concurrent use of medications with anti‐cholinergic properties and anti‐dementia medications in NHW and Native Hawaiians compared to Asian Americans 59 . Finally, several studies reported racial/ethnic differences in patterns of use of drugs for hypertension and other medical conditions in PLWD 46,60,61 .…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported on potentially inappropriate medication use—“drugs that should generally be avoided because they are ineffective or pose an unnecessarily high risk for older adults, and drugs that are appropriate to use in older persons only at certain doses, frequencies, or duration of therapies.” 58 One study reported higher rates of potentially inappropriate medication use in Hispanic Americans compared to NHW persons 58 and another found higher rates of concurrent use of medications with anti‐cholinergic properties and anti‐dementia medications in NHW and Native Hawaiians compared to Asian Americans. 59 Finally, several studies reported racial/ethnic differences in patterns of use of drugs for hypertension and other medical conditions in PLWD. 46 , 60 , 61 Among the studies of medication for other medical conditions, a Medicare Comprehensive Medication Review was found to reduce disparities in statin non‐adherence for Hispanic American PLWD.…”
Section: Resultsmentioning
confidence: 99%
“…One study showed that 35.4% of patients received these two drug types in combination [ 25 ]. The use of these medications in combination is likely to decrease their pharmacological benefit as they counteract each other [ 26 ], making their simultaneous use seldomly appropriate due to the drugs’ invalidating pharmacological effect [ 25 ].…”
Section: Introductionmentioning
confidence: 99%